Poor Sleep Quality Is the Risk Factor for Central Serous Chorioretinopathy - Yuying Ji; Miaoling Li; Xiongze Zhang; Yuting Peng; Feng Wen (Journal of Ophthalmology)
Purpose. Whether sleep disturbance is related with central serous chorioretinopathy (CSC) is still in controversy. This study is designed to investigate sleep status in CSC using definite and well-established methods. Methods. A total of 134 CSC patients and 134 age- and sex-matched normal controls were recruited in the study. Demographic data were collected through a questionnaire. Body mass index (BMI) was calculated by weight divided by height squared. The Pittsburgh Sleep Quality Index (PSQI) and Epworth Sleepiness Scale (ESS) were administered to all subjects to assess the sleep quality and daytime sleepiness, respectively. Depression Anxiety Stress Scales 21-item version (DASS-21) was also used to evaluate the emotion status as a positive control. Poor sleep quality was defined as PSQI > 5 and sleep apnea tendency as ESS > 10. Positive criteria scores were ≥10 for depression, ≥8 for anxiety, and ≥15 for stress. Results. There was no significant difference of BMI between the two groups (p=0.075). The prevalence of poor sleep quality (58.2% versus 23.9%; p<0.001) in CSC patients was significantly higher than normal. Specifically, CSC patients presented worse performance in certain components of sleep quality, that is, sleep latency, sleep duration, and sleep efficiency. More participants had stress (23.9% versus 3%, p<0.001), depression (25.4% versus 10.4%; p=0.001), and anxiety (28.4% versus 14.9%; p=0.008) emotions in CSC than that in normal. No significant difference was observed in sleep apnea tendency. Through logistic regression analysis, CSC patients were more likely to be in poor sleep quality (p<0.001; OR 3.608 (2.071–6.285)) and stress emotion (p=0.002, OR 6.734 (1.997–22.711)). Conclusion. Poor sleep quality is risk factor for CSC patients. Attention of sleep quality should be paid when treating them.